Comparative genomic analysis of the tricarboxylic acid cycle members in four Solanaceae vegetable crops and expression pattern analysis in Solanum tuberosum - Yongming Liu (BMC, 2021)
Abstract Background The tricarboxylic acid (TCA) cycle is crucial for energy supply in animal, plant, and microbial cells. It is not only the main pathway of carbohydrate catabolism but also the final pathway of lipid and protein catabolism. Some TCA genes have been found to play important roles in the growth and development of tomato and potato, but no comprehensive study of TCA cycle genes in Solanaceae crops has been reported. Results In this study, we analyzed TCA cycle genes in four important Solanaceae vegetable crops (potato (Solanum tuberosum), tomato (Solanum lycopersicum), eggplant (Solanum melongena), and pepper (Capsicum annuum)) based on comparative genomics. The four Solanaceae crops had a total of 180 TCA cycle genes: 43 in potato, 44 in tomato, 40 in eggplant, and 53 in pepper. Phylogenetic analysis, collinearity analysis, and tissue expression patterns revealed the conservation of and differences in TCA cycle genes between the four Solanaceae crops and found that there were unique subgroup members in Solanaceae crops that were independent of Arabidopsis genes. The expression analysis of potato TCA cycle genes showed that (1) they were widely expressed in various tissues, and some transcripts like Soltu.DM.01G003320.1(SCoAL) and Soltu.DM.04G021520.1 (SDH) mainly accumulate in vegetative organs, and some transcripts such as Soltu.DM.12G005620.3 (SDH) and Soltu.DM.02G007400.4 (MDH) are preferentially expressed in reproductive organs; (2) several transcripts can be significantly induced by hormones, such as Soltu.DM.08G023870.2 (IDH) and Soltu.DM.06G029290.1 (SDH) under ABA treatment, and Soltu.DM.07G021850.2 (CSY) and Soltu.DM.09G026740.1 (MDH) under BAP treatment, and Soltu.DM.02G000940.1 (IDH) and Soltu.DM.01G031350.4 (MDH) under GA treatment; (3) Soltu.DM.11G024650.1 (SDH) can be upregulated by the three disease resistance inducers including Phytophthora infestans, acibenzolar-S-methyl (BTH), and DL-β-amino-n-butyric acid (BABA); and (4) the levels of Soltu.DM.01G045790.1 (MDH), Soltu.DM.01G028520.3 (CSY), and Soltu.DM.12G028700.1 (CSY) can be activated by both NaCl and mannitol. The subcellular localization results of three potato citrate synthases showed that Soltu.DM.01G028520.3 was localized in mitochondria, while Soltu.DM.12G028700.1 and Soltu.DM.07G021850.1 were localized in the cytoplasm. Conclusions This study provides a scientific foundation for the comprehensive understanding and functional studies of TCA cycle genes in Solanaceae crops and reveals their potential roles in potato growth, development, and stress response.